2020
DOI: 10.1186/s40792-020-00888-9
|View full text |Cite
|
Sign up to set email alerts
|

Colonic varices treated with embolization after pancreatoduodenectomy with portal vein resection: a case report

Abstract: Background: Pancreatoduodenectomy with resection of the portal vein or superior mesenteric vein confluence has been safely performed in patients with pancreatic head cancer associated with infiltration of the portal vein or superior mesenteric vein. In recent years, left-sided portal hypertension, a late postoperative complication, has received focus owing to increased long-term survival with advances in chemotherapy. Left-sided hypertension may sometimes cause fatal gastrointestinal bleeding because of the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, it is important to note that colonic varices can also be seen with other diseases that cause portal vein occlusion, such as pancreatic cancer. [6][7][8][9] The gold standard for diagnosis is CT or selective mesenteric angiography, which can also be therapeutic with embolization in some cases. Often, these varices are diagnosed during colonoscopy for evaluation of lower gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that colonic varices can also be seen with other diseases that cause portal vein occlusion, such as pancreatic cancer. [6][7][8][9] The gold standard for diagnosis is CT or selective mesenteric angiography, which can also be therapeutic with embolization in some cases. Often, these varices are diagnosed during colonoscopy for evaluation of lower gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Splenectomy or splenic arterial embolization has been conventionally employed for gastric varices after SV occlusion [ 45 , 46 , 47 , 48 ], and recently, SV stenting has also been introduced as a safe and effective treatment for SPH-related gastrointestinal bleeding [ 49 ]. Similarly, several treatments combatting gastrointestinal bleeding for SPH after PD with PMSC resection have been reported [ 11 , 13 , 16 , 17 , 18 , 19 , 29 , 30 , 32 , 33 , 37 ]. At the point of determining the appropriate treatment, it is important to recognize the number of developed varicose veins and the location of the bleeding.…”
Section: Treatment Of Variceal Bleedingmentioning
confidence: 99%
“…Some studies indicated no gastrointestinal bleeding even after the incidence of varicose formation [ 10 , 14 , 18 , 21 , 26 , 27 , 28 ], but others reported the incidence of severe variceal bleeding [ 4 , 5 , 6 , 7 , 8 , 9 , 11 , 13 , 17 , 19 , 24 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. This difference may be due to the dedicated adjustment of SV pressure by collateral routes from the spleen.…”
Section: Pathogenesis Of Sphmentioning
confidence: 99%
See 1 more Smart Citation
“…Left-sided portal hypertension (LSPH) is thought to cause gastrointestinal varices and splenomegaly due to stenosis or obstruction of the splenic vein by various factors despite normal liver function and portal blood flow [ 1 , 2 ]. Colonic varices are rare and their treatment has not been standardized [3] , although cases of rupture and fatal hemorrhage have been reported [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%